Análisis del gobierno abierto en el desarrollo local de la parroquia rural San Antonio, período 2019-2021 - Mendoza Mejía, Rossy Selena (2023)
This research project begins with an analysis of Open Government in the local development of the rural parish of San Antonio during the period 2019-2021. Its objective is to propose an improvement plan to contribute to Open Government using the resources of the territory for the local development of the parish. This serves as an alternative that involves citizens in the process of responsible decision-making based on principles of participation. Additionally, the project aims to analyze the influence of Open Government on local development. To focus on the problem and weaknesses, evaluation tools were created, including an interview with the president of the parish council and a survey directed at a sample of the population. These instruments provided relevant information that served as the foundation to fulfill the stated objectives. The research employed inductive, deductive, and synthetic analytical methods. The results reflected the dissatisfaction of the residents due to unfulfilled promises within a specific timeframe, the lack of interest from authorities in the local development of the community, the limited enthusiasm in motivating citizens to participate in local development, and the improper use of parish resources. Due to these shortcomings, it is recommended to develop an improvement plan to contribute to and expedite processes, promote impartiality in services, enhance coverage, and provide opportunities for citizens to engage with Open Government using the resources offered by the locality for local development.